2016
DOI: 10.1016/j.maturitas.2016.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Animal and human models to understand ageing

Abstract: Human ageing is the gradual decline in organ and tissue function with increasing chronological time, leading eventually to loss of function and death. To study the processes involved over research-relevant timescales requires the use of accessible model systems that share significant similarities with humans. In this review, we assess the usefulness of various models, including unicellular yeasts, invertebrate worms and flies, mice and primates including humans, and highlight the benefits and possible drawback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 116 publications
(126 reference statements)
0
28
0
1
Order By: Relevance
“…Animal aging models have been at the forefront of aging research, and obtained a wealth of information, supporting investigators to discover pathways that drive human aging ( 4 ). Successful animal aging model include mice, rats, zebrafish and dogs ( 5 ). In the present study, we used beagle dogs as model animal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal aging models have been at the forefront of aging research, and obtained a wealth of information, supporting investigators to discover pathways that drive human aging ( 4 ). Successful animal aging model include mice, rats, zebrafish and dogs ( 5 ). In the present study, we used beagle dogs as model animal.…”
Section: Discussionmentioning
confidence: 99%
“…In order to understand the basic mechanism of aging as well as the physiopathological and behavioral effects of aging, aging studies range from the molecular level to the global organism level, from cell to the whole body, which are extensively investigated worldwide ( 2 , 3 ). Animal aging models are important for aging study, and several standard models have been established, including fruit fly, fish, birds, mouse, rats and dogs ( 4 , 5 ). Generally, aging models can be classified into two categories: naturally aging model and accelerated aging models ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic TOR (mTOR) pathway integrates somatotropic, nutritional and stress signals and plays a role in the control of autophagy and cell senescence. 46 While activation of mTOR signaling prevents cell death, promotes protein synthesis, growth and cell divisions, it apparently also accelerates aging. Blagosklonny and his colleagues suggested that aging can be viewed as “a continuation of developmental growth driven by genetic pathways such as mTOR”.…”
Section: Mechanistic Target Of Rapamycin (Mtor)mentioning
confidence: 99%
“…Based on many studies of aging and life span using various model organisms, it is becoming clear that some nutrient conditions, nutrient signals and related genetic mutations can have a remarkable effect on aging and life span control (Fontana, Partridge, & Longo, ; Lees, Walters, & Cox, ; Lin & Austriaco, ; Longo, Shadel, Kaeberlein, & Kennedy, ). Meanwhile, many studies have reported trying to artificially regulate aging and life span using various drugs, including rapamycin, metformin, resveratrol and myriocin (Kaeberlein, Creevy, & Promislow, ; Kennedy et al., ; Liu et al., ; Santos, Leitão‐Correia, Sousa, & Leão, ).…”
Section: Introductionmentioning
confidence: 99%